2022
DOI: 10.1016/j.isci.2021.103674
|View full text |Cite
|
Sign up to set email alerts
|

Quantum tunneling of hydrogen atom transfer affects mandrel degradation in inertial confinement fusion target fabrication

Abstract: Summary Poly-α-methylstyrene (PAMS) is considered as the preferred mandrel material, whose degradation is crucial for the fabrication of high-quality inertial confinement fusion (ICF) targets. Herein, we reveal that hydrogen atom transfer (HAT) during PAMS degradation, which is usually attributed to the thermal effect, unexpectedly exhibits a strong high-temperature tunneling effect. Specifically, although the energy barrier of the HAT reaction is only 10 −2 magnitude differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This result can be attributed to the lower chemical reaction activity of primary hydrogen compared to secondary and tertiary hydrogens ( Bruice, 2010 ). Moreover, the energy barriers of the above three reactions are smaller than that of the depolymerization reaction (approximately 0.70 eV in Ref Zhu et al., 2022 ), which means that these reactions can be performed at lower temperatures. This numerical simulation results are consistent with the results shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be attributed to the lower chemical reaction activity of primary hydrogen compared to secondary and tertiary hydrogens ( Bruice, 2010 ). Moreover, the energy barriers of the above three reactions are smaller than that of the depolymerization reaction (approximately 0.70 eV in Ref Zhu et al., 2022 ), which means that these reactions can be performed at lower temperatures. This numerical simulation results are consistent with the results shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers believe that the degradation of PAMS is initiated by free radicals generated from random chain scission ( Yu et al., 2015 ; Simha et al., 1950 ). Moreover, there is degradation uncertainty caused by quantum tunneling during thermal degradation ( Zhu et al., 2022 ). It should be noted that both the random chain scission and degradation uncertainty would lead to the degradation of PAMS deviating from the ideal depolymerization process and leaving residues.…”
Section: Introductionmentioning
confidence: 99%
“…This means that energy barriers are mainly determined by a structural reordering that takes place before the electronic activity starts to emerge. , Also, due to the shape of the energy profiles, the possibility of HAT by tunneling was evaluated. The WKB approximation was used for a rough estimation of the probability of tunneling using the formula: , , where w is the barrier width, m the reduced mass on the vibration mode of the imaginary frequency of the TS, V 0 is the potential barrier, E is the potential energy along the reaction path, and h is Planck’s constant. To obtain the barrier width, the IRC was computed in non-mass-weight Cartesian coordinates using units of length of Bohr.…”
Section: Resultsmentioning
confidence: 99%
“…The opportunity for a new explanation of this mechanism arrived with a breakthrough understanding of the quantum mechanical tunneling (QMT) effect in reactions. , As early as 1927, Hund proposed the notion of tunneling and concerned it in the configurational stability at stereogenic centers . Recently studies reported that the quantum effect may contribute significantly to reaction processes such as proton-coupled electron transfer reactions, enzyme redox reactions, and conformational inversions of molecules. More recent studies have determined that QMT plays a prominent role in the degradation of hydrocarbon polymeric material, even at temperatures above 300 K . In short, QMT in reactions has changed the way researchers think about many aspects of biological and chemical reactions, and therefore, the effect of QMT on the racemization process needs to be further investigated.…”
mentioning
confidence: 99%
“…26 Recently studies reported that the quantum effect may contribute significantly to reaction processes such as proton-coupled electron transfer reactions, enzyme redox reactions, and conformational inversions of molecules. 27−35 More recent studies have determined that QMT plays a prominent role in the degradation of hydrocarbon polymeric material, even at temperatures above 300 K. 36 In short, QMT in reactions has changed the way researchers think about many aspects of biological and chemical reactions, and therefore, the effect of QMT on the racemization process needs to be further investigated.…”
mentioning
confidence: 99%